The relationship between parenting styles, body image, and self-esteem of youth in Iceland - Lena Rún Daðadóttir 2001- (2024)
Parenting styles, body image, and self-esteem are key factors in understanding adolescents’ background and road to wellbeing. This study explores the relationships between these factors among Icelandic adolescents. Data used in this study is from a sample of 2000 participants from ages 13-16, in high schools nationwide. The study investigated how parenting factors such as shared time with parents, parental attentiveness, rules, regulations, and strictness, affect self-esteem and body image of teens. The data was analyzed using descriptive statistics, ANOVA, and a stepwise regression. The results revealed significant gender differences, with males reporting higher self-esteem and body image than females do. Both positive and negative effects of parenting practices were observed. Clear rules and parental strictness were positively associated with self-esteem and body image, while excessive shared time and attentiveness showed negative associations. No significant age effects were found, suggesting that these dynamics are consistent across developmental stages. These findings highlight the way parenting influences adolescent outcomes. This study aims to contribute to the understanding of adolescence development, highlighting the importance of positive parenting practices, providing valuable insights for parents and relevant institutions. Keywords: Parenting, adolescents, self-esteem, body image Uppeldisaðferðir, líkamsímynd og sjáflsálit eru lykil þættir í skilningi á bakgrunni unglinga og hvernig þeir öðlast vellíðan. Þessi rannsókn kannar tengsl þessara þátta meðal íslenskra unglinga. Gögn sem notuð eru í þessari rannsókn eru úr úrtaki 2000 þátttakenda á aldrinum 13-16 ára í framhaldsskólum á landsvísu. Rannsóknin kannaði hvernig uppeldisþættir eins og samverustundir með foreldrum, athygli foreldra, reglur, reglugerðir og strangar uppeldisaðferðir hafa áhrif á sjálfsálit og líkamsímynd unglinga. Gögnin voru greind með því að nota lýsandi tölfræði, ANOVA og þrepaskipta aðhvarfsgreiningu. Niðurstöðurnar benda til ...